Pengembangan Pakan Komplit Berbasis Sorgum Untuk Penguatan Agribisnis Lokal Di Kabupaten Subang - Desty Dwi Sulistyowati; Romalasari Atika; Juriyah Astika Dewi (AGRISUSTAIN : Journal of Agribusiness and Sustainable Agriculture, 2025)
The advancement of sustainable livestock practices in Indonesia is persistently challenged by deficits in the feed value chain, namely availability, quality, and affordability, with pronounced effects on smallholder productivity. Subang Regency, West Java, has strong potential for developing sorghum (Sorghum bicolor L. Moench) as a locally based complete feed resource due to its adaptability to marginal lands and climate variability. This article aims to analyze the development of sorghum-based complete feed and its role in strengthening local agribusiness through a region-based collaborative approach. A qualitative descriptive method was employed using secondary data from scientific literature, policy documents, and official publications from 2024–2025. The results indicate that integrating sorghum into complete feed systems improves feed-use efficiency, reduces production costs, and strengthens local agribusiness value chains. This development is supported by multi-stakeholder collaboration involving research institutions, industry, educational institutions, and farmer groups, forming an inclusive agribusiness innovation ecosystem. Such collaboration enhances technology adoption, institutional capacity, and rural economic opportunities. In conclusion, the development of sorghum based complete feed represents a promising agribusiness strategy to support sustainable livestock systems and local economic strengthening in Subang Regency, with strong potential for replication in regions with similar agroecological conditions.